ANALISIS LABELISASI HALAL DALAM ETIKA BERBISNIS [STUDI KASUS PADA UKM SENTRA ROTI BABAKAN RAHAYU DI KOTA BANDUNG] - Yuyun Yuniarti; Ali Anwar Yusuf (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2023)
Halal products are one part of business development based on business ethics, one of the efforts to maintain the halalness of products, it requires good cooperation between producers, government, and consumers. This is in accordance with what is stated in the teachings of the Islamic religion which encourages every business actor, especially in the food sector to maintain the halalness of the product.The Babakan Rahayu Bread UKM Center is one of the businesses engaged in the culinary field, at this time not all of the activities of producing halal bread are guaranteed halal products. For this reason, researchers are interested in conducting research related to the halalness of products related to the application of business ethics in that place.The research method used is descriptive analysis, which is a method to examine, observe, and conduct interviews with informants, namely business actors, cooperative heads, consumers, and the Bandung City MSME Cooperative Office as one of the agencies that guarantees the halalness of products.The results showed that the bread-making activities in the bakery center in Babakan Rahayu, Bandung, turned out that the business actors did not really feel the importance of halal certification but most of them had carried out business activities based on business ethics principles, especially those concerning employee management, business development, and advertising (marketing). product)Suggestions that researchers convey include increasing business awareness in encouraging halal certification, it requires encouragement / motivation from various parties so that all business actors in the place are more aware of halal certification.Keywords: product halalness and business ethics.